An investigation into staff and pupil views of a character education programme in a comprehensive academy - Duggan, Ruadh (2016)
There has been increasing concern from many sources regarding character development in children and adolescents. As a result, it has been decided that character education should take a more prominent role in the educational arena. A growing number of schools have therefore introduced character education programmes, including the school where I teach. This investigation explored staff and pupil views regarding the implementation of the school’s new character education programme. Two pupil populations (Year 7 and Year 10) were administered an online questionnaire and a smaller number of teaching staff were both interviewed and given a similar questionnaire. The investigation involved 190 Year 7 pupils, 117 Year 10 pupils, and 9 teachers. It was found that the two pupil groups shared many similar views with regards to character education. On the whole these were positive, although the Year 10s reported less favourably in some areas, as compared with Year 7s who have had a greater exposure to character education. Teachers were found to have very positive views, although they did indicate areas where the programme could be improved. Despite its limitations, this investigation provides a valuable ‘snapshot’ of the current views of character education in a single school, at a particular time.